Localized delivery of gel-embedded siRNA nanoparticles for pancreatic cancer treatment: Formulation, biodistribution and bioactivity in mice - Majd Agbaria; Doaa Jbara-Agbaria; Gershon Golomb (Precision Nanomedicine)
Pancreatic cancer (PC) is one of the most lethal malignancies, primarily due to its dense extra-cellular matrix and poor vascularization, which limit effective drug accumulation and therapy. Here, we describe a local siRNA delivery system using thermosensitive hydrogel-embedded na-noparticles (NPs). siRNA against VAV1 (siVAV1), a key protein implicated in PC, was encapsu-lated in poly(lactic-co-glycolic acid) (PLGA)-based NPs decorated with an ApoB-derived peptide as the targeting ligand. The ApoB-targeted NPs exhibited optimal physicochemical properties, including nanoscale size, low polydispersity index, and a neutral charge. The sustained-release siRNA-NPs were incorporated into a thermosensitive hydrogel (poloxamer) and locally injected into the pancreas of tumor-bearing mice. Treatment with targeted NPs in gel (tNPs@G) resulted in a notable increase in accumulation within the tumor (1.9-fold) and spleen (1.3-fold) 72 hours post-injection, with minimal systemic exposure and no local cytotoxicity. Intra-tumoral implan-tation of the gel-laden siVAV1 NPs in PC-bearing mice led to a significant reduction in tumor growth and volume (2.6-fold), mediated by the inhibition of both VAV1 mRNA and protein, and improved survival rates. The developed local siRNA delivery system provides a minimally in-vasive and effective therapeutic approach for PC, addressing key drug delivery barriers.